Rate and risk factors of in-hospital and early post- discharge mortality in patients admitted to an internal medicine ward. Issue 1 (2023) - Lenti, Marco Vincenzo; Croce, Gabriele; Brera, Alice Silvia; Ballesio, Alessia; Padovini, Lucia; Bertolino, Giampiera; Sabatino, Antonio Di; Corazza, Catherine Klersy; Gino Roberto
No abstract available